IMPROVING STUDENTS’ SPEAKING SKILL OF THE FIFTH GRADERS IN SD INSAN AMANAH MALANG THROUGH DRAMA METHOD - Suhardini Nurhayati; Abdul Syukur Ghazali; Maryaeni Maryaeni; Roekhan Roekhan (Jurusan Sastra Indonesia, 2019)
This study aims to provide a problem-solving about students’ reluctance in speaking activities to express thoughts and feelings in SD Insan Amanah. There were several problems that inhibit the students’ speaking skills, namely fear of expressing, difficulties in facing many people (stage fright), wrong perceptions, and lack of contextual understanding. The drama method is impressive since it attracts people, which may encourage an unpredictable power when people perform it together. During the process, the students were expected to increase speaking skills; namely, the students are capable of speaking with proper pronunciation, intonation, and expressions. The research data source was the students’ work in the form of structural cards and drama scripts. The data collection in this study was employed through observation format, field note format, structural cards, and drama scripts. Meanwhile, the data analysis was implemented through data reduction, data presentation, and conclusion. Peer observation and examination were conducted to test the data validity. Based on the research findings, in general, it can be concluded that the speaking skills learning through drama method of the fifth graders in SD Insan Amanah Malang were proved to increase. In Cycle I, only 35% of students succeeded. However, in Cycle II, there was an increase in 90% of students who succeeded in Basic Competence of